(untitled) (American Journal of Islam and Society, 2003)
The Case It was with great pleasure that I accepted the invitation from Dr. Yahya Mahmud bin Junayd and Dr. Awadh al-Badi to be with you today. I am very happy to be able to speak to you on this special occasion about an important and very large topic: the Arabic cultural influence on the Balkans. I am particularly glad to be speaking on this theme in the hall of this eminent institute, the King Faisal Centre for Islamic Studies and Research. I will begin by saying that I shall not deal at length with either the history or the geography of the Balkans, for I am justified in assuming that the audience I am addressing today is familiar with these, at least in outline. I shall therefore proceed at once to the topic itself. Arabic and Islamic influences began to reach the Balkan peninsula well before the Turks and the start of Ottoman imperial rule in the fifteenth century. Museums throughout the Balkans still contain items from the period of the first contacts of the Balkan peoples with the Arabs of Sicily, southern Italy, and al-Andalus. We thus find Arabic utensils, for example the ibrig,1 which we also call ibrik, with exactly the same meaning in Bosnian as in Arabic. It is the same in the Serbian and Croatian languages, too. The archives of Dubrovnik contain a large collection of Arabic manuscripts that show clearly what kind of goods were traded between Arab traders and those of the Balkans over many centuries. But Arab traders did not only bring with them Arabic customs, books, items, ideas, and principles; the Slavs themselves, who served first in the military with the Arabs ...